Uma Ontologia CIDOC-CRM para o Museu Virtual da Emigração - Martini, Ricardo G.; Araújo, Cristiana; Henriques, Pedro Rangel (Revista ComInG - Communications and Innovations Gazette, 2016)
In this article we describe the use of the international standard for museum ontologies, CIDOC-CRM, to build a concrete ontology for ME, a virtual museum for the Emigration phenomena. Although the digital document repository is a conventional relational database, more abstract data models should be used to enable conceptual navigation over the information to help end-users (the museum visitors) to extract knowledge from the navigation (the visit). Thus, we will emphasize the design of a Reduced CRM-compatible form to describe the objects of our assets (people that emigrate in some moment to some other country), and the relations holding among them that better express the emigration movements. We also discuss the choice of RDF to expose the ontology triples via Apache Jena Fuseki server, a SPARQL end-point accessible over HTTP, and an engine (Jena ARQ) to query the RDF data. Finally, it was possible to transform these data into RDF and apply SPARQL queries, returning the desired results.